STUDY OF MAGNETIC SUSCEPTIBILITY OF IRON - OXALATE COMPOUNDS - PRABOWO H. (NIM: 20507069), EKO
Magnetic susceptibility is a ratio of the magnetic interaction of substance to the external magnetic field. Magnetic susceptibilities of the three compounds containing iron and oxalic ions, such as Fe(ox).2H2O, K3[Fe(ox)3].3H2O and [Fe(bipy)3][FeFe(ox)3] have been studied. Their magnetic susceptibilities for solid and solution samples were measured using Magnetic Susceptibility Balance (MSB). The magnetic susceptibility of Fe(ox)2.2H2O was 4,0 cm3 K mol-1 in the solid sample and 3,6 cm3 K mol-1 in 0,1 M solution sample. The data indicate that iron(II) in the high spin state. The magnetic susceptibility of K3[Fe(ox)3].3H2O was 4,6 cm3 K mol-1 in the solid sample, this is exactly correct for iron(III) in high spin state. The magnetic susceptibility of [Fe(bipy)3][FeFe(ox)3] was 3,1 cm3 K mol-1, this value is agree with previous data obtained for iron(II) in multinuclear complex. The magnetic susceptibilities of K3[Fe(ox)3].3H2O and [Fe(bipy)3] [FeFe(ox)3] in solution samples are observed slightly lower than the expected values, this is due to the low solubility of the compounds in water. Three factors that affecting the magnetic susceptibility measurement are rubber ring position, sample length and packing. The rubber ring position and the sample length are interconnected each other. For sample length more than 1 cm, the optimum position of rubber ring is 4,7 cm. However, for sample length less than 1 cm, the optimum position rubber ring is 4,3 cm. Those data have been observed for well packing sample.